QUESTION -ANSWER RELATIONSHIP (QAR) AS A STRATEGY TRAINING TO IMPROVE STUDENT’S READING COMPREHENSION OF NARRATIVE TEXT - Anggraini, Desti (RETAIN, 2021)
Reading comprehension is a complex activity that requires the prior knowledge of the readers to grasp the information’s details contained in the passage. It is one of the challenges that students in senior high school face in comprehending the text's meaning. They have lack of reading comprehension which makes them difficult to grasp and find important information contained in a text. As a result, it makes the teacher must use a proper and effective strategy for assisting students to conceive and comprehend the text. Therefore, this study focused on the Question-Answer Relationship (QAR) as a strategy training to improve student’s reading comprehension in narrative text and discover the student’s responses after applying QAR in the classroom activity. The result of this study showed that QAR as a strategy training is useful and effective for improving student’s reading comprehension ability in the class. The students became better at responding comprehension questions in the narrative text. This strategy also promoted students to be more attentive in class and increased student’s confidence to answer questions and differentiate questions about the text they had read.